Lactate-associated gene MCU promotes the proliferation, migration, and invasion of pancreatic ductal adenocarcinoma - Yuhang Chen; Fenglin Zhang; Suoyi Dai; Jiangang Zhao; Wenxun Cai; Ke Zhang; Xinghe Liao; Lianyu Chen (BMC Cancer)
Abstract Background The metabolism of lactate and lactylation of proteins are believed to influence tumor development through their effects on the tumor microenvironment and immune escape mechanisms. Nevertheless, its significance in pancreatic ductal adenocarcinoma (PDAC) has yet to be fully understood. This investigation sought to assess the predictive value and treatment implications of lactate-related genes (LRGs) in PDAC. Methods We analyzed PDAC data from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO), identifying LRGs. Using weighted gene co-expression network analysis (WGCNA) and consensus clustering, we delineated lactate subtypes and extracted differentially expressed genes. Functional enrichment and gene set enrichment analysis (GSEA) analyses were conducted to explore pathways. A lactate-linked risk signature was constructed using Lasso-Cox regression, and its prognostic value was validated. In vitro experiments were executed to examine the function of MCU in PDAC cells. In vitro experiments were conducted to detect the malignant potential of MCU in PDAC cells and its effect on lactic acid metabolism. Results Two lactate subtypes were identified, with distinct gene expression profiles and clinical outcomes. The risk signature, comprising four LRGs, predicted survival with significant accuracy. In vitro, MCU knockdown reduced cell proliferation, migration, invasion, and stemness, confirming its role in PDAC malignancy. At the same time, it can also inhibit lactate production and glycolysis processes. Conclusion Our investigation underscores the importance of LRGs in PDAC, providing a novel prognostic signature and therapeutic target.